Conflicting Authority over Asset Seizure in Tax, Corruption, Bankruptcy - Mahanto Aminanto; Paduanta Hutahayan; Bachtiar Arifin; Anton Rudhianto (Universitas Negeri Semarang, 2025)
This study aims to analyze the conflict of asset seizure authority involving the Directorate General of Taxes, the Attorney General's Office, and the Bankruptcy Trustee in the bankruptcy proceedings of PT Mount Dreams Indonesia. The main focus of this research is on asset seizures conducted by the Directorate General of Taxes as part of criminal tax investigations pursuant to Article 44 paragraph (2) letter j of the Law on General Provisions and Tax Procedures (UU KUP). The existence of overlapping lex specialis regulations in the fields of taxation, corruption, and bankruptcy law has led to conflicts of authority between law enforcement agencies in executing asset seizures. This study employs normative juridical methods using statutory, doctrinal, and Gustav Radbruch’s substantive justice theory approaches. The findings indicate that the absence of inter-agency coordination norms and the lack of harmonization among sectoral lex specialis regulations are the main causes of authority conflicts over asset seizures in bankruptcy proceedings. Furthermore, the expansion of asset recovery instruments operated independently by each agency, without integration into the bankruptcy estate, exacerbates conflicts over asset control. This research recommends the establishment of inter-agency coordination norms for asset seizure authority, strengthening renvoi as a unified verification forum, integrating asset recovery results into the bankruptcy estate, and enhancing the principle of substantive justice in the regulation of bankruptcy settlement.